Does Social Security crowd out Private Savings? The Case of Bismarck's System of Social Insurance - Sibylle Lehmann-Hasemeyer; Jochen Streb (IBF - Institut für Bank- und Finanzgeschichte, 2017)
Imperial chancellor Bismarck's system of social insurance (with its three pillars health, accident and pension insurance) was an important role model for social security systems across Europe and in the US. How the introduction of the German system changed economic expectations and decisions of the German workforce has not been researched, though. This article closes this gap by analyzing the development of Prussian savings banks' deposits in the late 19th century with the help of a difference-in-difference-like approach. We show that, in the Prussian case, social security crowded out private savings considerably. As counterfactual voluntary savings would have been far from sufficient, however, Bismarck's social insurance system was still needed to fight the misery workers and their families potentially faced in old age or times of sickness.
Keywords: D14; E21; H55; N33; 330